Mutational biosynthesis of neomycin analogs by a mutant of neomycin-producing Streptomyces fradiae - Shi, Guanying; Zhang, Xingang; Wu, Lang; Xie, Jin; Tao, Ke; Hou, Taiping (Folia microbiologica, 2011)
Neomycin, produced by Streptomyces fradiae, has been widely used for the treatment of bacterial infections in clinical and agricultural applications. In this study, a neomycin nonproducing mutant of S. fradiae was obtained by gene disruption technique for mutational biosynthesis. A crucial gene neoC (neo7) which encodes 2-deoxystreptamine (2-DOS) synthases was disrupted. The mutant could resume producing neomycin in the presence of 2-DOS. Salen derivatives of 2-DOS were synthesized and individually added to cultures of the mutant. Antibacterial activity of the mutasynthesis products against Staphylococcus aureus and four plant pathogenic bacteria (Pseudomonas solanacarum, Erwinia carotovora, Xanthomonas oryzae, and Xanthomonas campestris) was detected quantitatively by Oxford cup method. It is suggested that all 2-DOS derivatives were incorporated by the mutant into new active neomycin analogs except for 2-DOS derivative 2d ((1R,2r,3S,4R,6S)-4,6-bis((E)-3,5-di-tert-butyl-2-hydroxybenzylideneamino)cyclohexane-1,2,3-triol). Neomycin analogs produced by feeding 2-DOS derivative 2a ((1R,2r,3S,4R,6S)-4,6-bis((E)-2 hydroxybenzylideneamino)cyclohexane-1,2,3-triol) to cultures of the mutant displayed a similar antibacterial activity with neomycin produced by wild strain.
Keywords: mutace; bakteriální proteiny; Bacterial Proteins; Molecular Structure; molekulární struktura; antibakteriální látky; neomycin; Anti-Bacterial Agents; Mutation; Neomycin; Streptomyces